Development and implication of a two-tier thermodynamic diagnostic test to survey students' understanding in thermal physics - Chanwit Kamcharean (2018)
This study aimed to develop, implement and evaluate a conceptual survey, the Thermodynamic Diagnostic Test (TDT), covering the three fundamental laws of thermodynamics. The test consisted of 15 two-tier multiple-choices questions, with a first tier of content-based questions and a second of reasoning-based questions. The development of TDT combined both qualitative and quantitative methods, investigating student reasoning, and their reasons were then used to develop the second tier questions. The 1st version of the test was administered to 48 students taking a fundamental physics course and their responses used to improve and develop the final version of the TDT, which was then administered to a further 46 students the next academic year. The student responses on the final version of TDT were analyzed in terms of their alternative concepts. Nine alternative concepts in three laws of thermodynamics were identified. There were three predominant alternative concepts regarding "heat and temperature", "increasing temperature causes increase in pressure" and "entropy always increases." Therefore, these results indicated that the two-tier multiple choice questions are effective in diagnosing alternative conceptions in thermodynamics.